ANALISIS KOMPARASI USAHATANI PADI SAWAH PENGGUNA BENIH BERSERTIFIKAT DAN BENIH NON SERTIFIKAT DI KELURAHAN KEMUMU KECAMATAN ARMA JAYA KABUPATEN BENGKULU UTARA - Raditya, Reza; Asriani, Putri Suci; Sriyoto, Sriyoto (Jurnal AGRISEP, 2015)
This research purposse are to calculate and compare the productivity of land, income, and efficiency between paddy farming using certified seed and paddy farming which uses non-certified seed. The research was conductedin the village of Kemumu with a total sample of 15 farmers certified seed specified users using census method and 22 non-certified seed user farmers were determined using purposive sampling method. Methods of data analysis using quantitative analysis and qualitative (descriptive). The analysis showed that the average productivity of the land (5,112 Ton/Ha), average income (Rp 16.501.384,77/Ha), and the average efficiency (3,91) forpaddy farming using certified seed. While the average productivity of the land (3,918 Ton/Ha), the average income (Rp 10.951.035,29/Ha), and the average efficiency (3.24) for paddy farming which uses non-certified seed. Based onthe results ofthe analysis, itcan be concluded that certified seed is better than non-certified seed both in terms of land productivity, income, and efficiency.